Curricular planning and its influence on the development of the basic linguistic skills of the english language at the “Jaime Roldós Aguilera” night high school, academic year 2009-2010 - ESPAÑA MINGA, CARMEN SUSANA (2010)
The present research work titled: ―CURRICULAR PLANNING AND ITS INFLUENCE ON THE DEVELOPMENT OF THE BASIC LINGUISTIC SKILLS OF THE ENGLISH LANGUAGE AT THE ―JAIME ROLDÓS AGUILERA‖ NIGHT HIGH SCHOOL, ACADEMIC YEAR 2009-2010‖, its general objective is ―to determine how the Curricular Planning affects in the development of the Basic Linguistic Skills of the English Language in the students of the Jaime Roldós Aguilera Night High School, academic year 2009-2010‖. To develop the field work we applied the instrument of the survey to the teachers and students; to process the information we used scientific, analytic-synthetic, and explicative methods which helped us to represent the information in a descriptive way. The hypotheses that guided this research work were two: ―The Mesoplanning is not elaborated by the teachers considering the development of the Basic Linguistic Skills of the English Language in the students, and ―The Microplanning does not take into account the development of the Basic Linguistic Skills of the English Language in the students at the ―Jaime Roldós Aguilera‖ High School. The main results in the different items of the survey showed that the mesoplanning is not elaborated by the teachers considering the development of the Basic Linguistic Skills of the English Language, in the same way the microplanning does not take into account the development of the basic linguistic skills of the English Language. Finally, the Didactic Unit Plan and Lesson Plan are not elaborated taking into account the most important elements which are skills for the development of the teaching-learning process of the English Language.